1996
DOI: 10.1063/1.116419
|View full text |Cite
|
Sign up to set email alerts
|

Patterned self-assembly of one-dimensional arsenic particle arrays in GaAs by controlled precipitation

Abstract: A process for the patterned self-assembly of nanometer-scale particles within a solid is described. The process uses crystal strain and composition to guide the formation of arsenic precipitates in GaAs-based epitaxial layers grown at low temperature by molecular beam epitaxy. The lateral particle position is controlled by the strain produced by a surface stress structure while the vertical position is controlled by the epitaxial layer composition. Arsenic particles ∼16-nm in diameter are fabricated in one-dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…35,36 Analogously, the controlled assembly of MnAs precipitates within the GaAs matrix using surface stressors appears feasible. The precipitates elastically interact with the stress field of the matrix.…”
Section: Discussionmentioning
confidence: 99%
“…35,36 Analogously, the controlled assembly of MnAs precipitates within the GaAs matrix using surface stressors appears feasible. The precipitates elastically interact with the stress field of the matrix.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 We are studying applications in this self-assembly technique to the fabrication of single-electron tunneling devices in which the arsenic particles serve as small metallic islands separated by GaAs tunneling barriers. 1,2 It has been shown that the position of particles in the growth direction can be controlled by composition while the lateral position can be controlled by strain produced by a surface stress structure.…”
Section: Annealing Cycle Dependence Of Preferential Arsenic Precipitamentioning
confidence: 99%
“…Generally, photoresist processing and etching follow to form the final structures. 4 However, the main challenges of all self-assembly techniques are precise control of the dimensions of the structures and reproducibility. Thus alter native approaches are under investigation, including different self-assembly tech niques.…”
Section: Introductionmentioning
confidence: 99%